2020
DOI: 10.21608/sjfop.2020.96213
|View full text |Cite
|
Sign up to set email alerts
|

Improving Rooting and Growth of Conocarpus Erectus Stem Cuttings Using Indole-3-Butyric Acid (Iba) and Some Biostimulants

Abstract: The current study was conducted to evaluate the effects of indole-3-butyric acid (IBA) at 100 ppm with or without biostimulants (Agrobacterium rhizogenes, seaweed extract and coconut water) as either a spray or drench for 3 minutes or 1 hour on rooting and growth parameters of three cutting types (tip, middle and basal) of Conocarpus erectus L. The data showed that the rooting percentage, root and vegetative characteristics of rooted cuttings were significantly increased by all treatments of IBA and/or biostim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…[74]. Similar results were obtained by [75,76], who found that treating tip cuttings with IBA or bio-stimulants enhanced measures of the roots and shoots compared to untreated cuttings.…”
Section: Shoot Lengthsupporting
confidence: 75%
See 1 more Smart Citation
“…[74]. Similar results were obtained by [75,76], who found that treating tip cuttings with IBA or bio-stimulants enhanced measures of the roots and shoots compared to untreated cuttings.…”
Section: Shoot Lengthsupporting
confidence: 75%
“…Also, the same plant extract at 75% gave a subsequent positive effect, followed by willow extract at 100%, while treating cuttings with 2000 ppm NAA produced precisely the significantly lowest values of root fresh and dry weight in both seasons compared with the other treatments. These results may be attributed to aloe and willow extracts, which appear to have plant hormone properties, e.g., salicylic acid [28,58], which is related to the regulation of root growth and development [76,77]. Also, it has been shown that exogenous SA improves the actions of the endogenous rooting hormone IAA, which results in the motivation of DNA, RNA, and protein synthesis [55,66].…”
Section: Root Fresh and Dry Weightmentioning
confidence: 99%
“…Similar results were found by Amri et al (2010), who showed that the use of IBA promoted the rooting of Dalbergia melanoxylon (granadilla). Other ornamental species where IBA has been used successfully are Hibiscus rosa-sinensis L., Conocarpus erectus, Rosa caninna L., Carisa carandas L., Streptosolen jamesonii, and Solidago et al, 2020;Tanuja and Rana, 2018;Pêgo et al, 2019). IBA, a synthetic auxin, is commonly applied to various woody species for root generation because it regulates cell division, expansion, and differentiation (Frick and Strader, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Indole Butyric Acid (IBA) is the most significant of these auxins; it differs from other auxins in that it is less harmful to plant tissue and more efficient in forming roots [18,19]. IBA is more stable than other rooting chemicals and promotes faster rooting together with larger and more numerous roots, resulting in future seedling success [20,21,22]. The aforementioned information served as the basis for this study's testing of several mixes of chemical and natural rooting agents in order to identify the best treatments in terms of root features and the degree to which two distinct pomegranate varieties responded to these mixes.…”
Section: Introductionmentioning
confidence: 99%